Prevalence and associated factors of underweight, overweight, and obesity Among Bangladeshi adults: An analysis of demographic and health survey 2017-18 - Gupta, Rajat Das; Al Kibria, Gulam Muhammed (Science Direct, 2022)
This article was published in Obesity Medicine by Elsevier [© 2021 Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/j.obmed.2021.100342 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S2451847621000257